Tegangan Ambang pada Sambungan Las CDW antara Baja dan Kuningan dalam Lingkungan Korosif - Lobo, Osmar Buntu; Darmadi, Djarot Bangun; Novareza, Oyong (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
Failure at the welded joint can be occurs due to the Stress Corrosion Cracking (SCC) phenomenon. Dissimilar welding is more susceptible to SCC when compared to similar welding. This can be occurs because the material or metal that connected is non-homogeneous material. which causes the material will be difficult to be combined perfectly. This study aims to determine the threshold stress (ÏƒTh) at the dissimilar welded joint between steel and brass which have SCC loads. Both materials were connected by the welding method by using a Capacitive Discharge Welding (CDW) welding machine. Surface preparation or surface treatment is applied to one of the basic materials (low carbon steel) to obtain optimal joint results. The welded joint was tested by using Constant Load Test (CLT) methods, which is engineered in such a way that the welded joint get the stress, Â corrosive environment (1M NHO3 solutions) and voids produced by the weld joint itself. The result shows that the threshold stress of the dissimilar welding joint between steel and brass by the CDW method is 330 MPa.